Serum YKL‐40, a prognostic marker in patients with large‐artery atherosclerotic stroke. (21st September 2016) - Chen, X.‐L.; Li, Q.; Huang, W.‐S.; Lin, Y.‐S.; Xue, J.; Wang, B.; Jin, K.‐L.; Shao, B.
Abstract : Background and purpose: Inflammation comprises important aspects of large‐artery atherosclerosis (LAA) stroke pathophysiology. YKL‐40 is a new and emerging biomarker that is associated with both acute and chronic inflammations. Elevated serum concentrations of YKL‐40 have been reported in patients with atherosclerosis and other cardiovascular diseases. This study investigates whether serum YKL‐40 concentrations on admission can predict 3‐month clinical outcomes after LAA stroke. Methods: We recruited control patients (n=85) and those with LAA stroke (n=141) according to the TOAST classification system. The modified Rankin scale at 3 months after stroke was used to evaluate the prognosis. The prognostic accuracy was assessed by the receiver operating characteristic curve. Results: Serum YKL‐40 level was significantly higher for LAA patients than for controls ( P <.001). Patients with poor outcomes (n=36) had significantly increased serum YKL‐40 concentrations on admission ( P =.01). High YKL‐40 levels predicted poor functional outcome (OR=6.47, P =.02). Moreover, the combination of YKL‐40 level and the NIHSS score could improve the prognostic accuracy of the NIHSS in predicting functional outcome (combined areas under the curve, 0.87; 95% CI, 0.80‐0.94; P <.001). Conclusions: The level of serum YKL‐40 is a significant and independent biomarker to predict the clinical outcome of LAA stroke.